2016
DOI: 10.1093/jhps/hnv071
|View full text |Cite
|
Sign up to set email alerts
|

The role of arthroscopy in the dysplastic hip—a systematic review of the intra-articular findings, and the outcomes utilizing hip arthroscopic surgery

Abstract: Acetabular dysplasia is one of the most common sources of hip arthritis. With the recent innovation in hip arthroscopy, the question has been raised whether arthroscopy can be used to treat dysplastic hip conditions. The purposes of this systematic review are (i) describe the prevalence of intra-articular pathologies and (ii) report the outcomes of dysplastic hip treatment with hip arthroscopy as a sole treatment. Medical databases were searched for articles including arthroscopic findings and treatment of dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
(39 reference statements)
0
35
0
Order By: Relevance
“…The use of hip arthroscopy, as a stand-alone procedure, to address labral pathology in the setting of acetabular dysplasia remains controversial. A recent systematic review, reported on 13 studies on the role of arthroscopy in the dysplastic hip [ 18 ]. The authors concluded that arthroscopic treatment of mild dysplasia could yield satisfactory results whereas treatment of more dysplastic hips is controversial, with no evidence of optimal results for hips with a center edge angle <20°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of hip arthroscopy, as a stand-alone procedure, to address labral pathology in the setting of acetabular dysplasia remains controversial. A recent systematic review, reported on 13 studies on the role of arthroscopy in the dysplastic hip [ 18 ]. The authors concluded that arthroscopic treatment of mild dysplasia could yield satisfactory results whereas treatment of more dysplastic hips is controversial, with no evidence of optimal results for hips with a center edge angle <20°.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that arthroscopic treatment of mild dysplasia could yield satisfactory results whereas treatment of more dysplastic hips is controversial, with no evidence of optimal results for hips with a center edge angle <20°. [ 18 ] Parvizi et al reported on 34 patients with a diagnosis of acetabular dysplasia who had undergone isolated hip arthroscopy for labral injury. Seventy percent failed to obtain pain relief, 79% progressed to OA and 47% required an additional open surgical treatment [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though select exceptions (e.g. dynamic impingement, micro instability) [ 63 ], most hip arthroscopy experts caution against the use of arthroscopic surgery in setting of acetabular dysplasia, especially with center-edge angles less than 20 degrees [ 64 ], while borderline dysplasia is also cautioned [ 3 ]. In a study of 58 patients who failed hip arthroscopy and were treated with either arthroscopic or open revision procedure, 24% hips of the hips were determined to have dysplasia and were subsequently treated with acetabular reorientation via the Bernese periacetabular osteotomy (PAO) [ 65 ].…”
Section: Inappropriate Indications: Arthritis and Hip Dysplasiamentioning
confidence: 99%
“…From the literature, numerous studies have agreed that limited joint space and severe dysplasia are contraindications. 2,3 A study titled "Hip Arthroscopy in Patients Age 40 or Older: A Systematic Review" by Horner, Ekhtiari, Simunovic, Safran, Philippon, and Ayeni 4 looks at what the literature thinks about age and outcomes after hip arthroscopy.…”
Section: See Related Article On Page 464mentioning
confidence: 99%